ANALISIS PRIORITAS KEPENTINGAN DALAM PENENTUAN SISTEM PERSENJATAAN PADA PTTA MALE - zaldiansyah zaldi; Y.H Yogaswara; Yayat Ruyat (ELEMEN : JURNAL TEKNIK MESIN, 2023)
The weapon system's modernization is expected to anticipate a very conditional and fluctuating defense situation. One is developing Medium Altitude Long Endurance Unmanned Aircraft (PTTA MALE) vehicles by completing weapons systems to strengthen the national defense system. This study analyzes the technical specifications of weapons systems that meet user needs at PTTA MALE. This study uses qualitative and quantitative methods with research analysis using a Quality Function Deployment (QFD) approach. The analysis is carried out based on the priority scale value reference from the technical specifications of the user requirements. The research results obtained priority scale of operational requirements and technical specifications of weapons systems based on Benchmark Performance (BP) values, namely weapon load (84.31%), warheads (80.39%), guidance systems (68.63%), sensors ( 68.63%), target distance (68.63%), based on independence (63.40%), target type (63.40%), and explosion range (49.02%).